Evidence for the Use of Tranexamic Acid in Subarachnoid and Subdural Hemorrhage: A Systematic Review - Anker-Møller, Thorkil; Troldborg, Anne; Sunde, Niels; Hvas, Anne-Mette (Seminars in Thrombosis and Hemostasis, 2017)
Despite neurosurgical treatment, a subarachnoid hemorrhage (SAH) can cause a debilitating stroke. The case fatality rate ranges from 27 to 44%, and many survivors are left permanently disabled; therefore, the need for improved treatment is obvious. Furthermore, subdural hemorrhages (SDHs) have a cumulative recurrence rate of 14% in the first year and are potentially fatal. The aim of this systematic review is to assess and discuss the evidence for the role of tranexamic acid (TXA) in treatment of SAH and SDH. Systematic literature searches were performed in MEDLINE, Embase, Scopus, and Web of Science (1946–2016). The inclusion criteria were TXA-treated group and control group; SAH or SDH verified by imaging, intraoperatively or at autopsy; human subjects; English; and an objective outcome. The search terms matched 443 records. Eight studies including nontraumatic SAH patients and one study including traumatic intracranial bleeding met the inclusion criteria. Comparing TXA-treated nontraumatic patients with controls, we found an overall odds ratio (OR) for rebleeding of 0.41 (95% confidence interval [CI]: 0.26–0.64), six studies reported the mortality rate with an overall OR of 0.88 (95% CI: 0.68–1.12), four studies reported no statistically significant difference on the Glasgow Outcome Scale, and one study showed a statistically significant increased risk of cerebral ischemia, whereas seven studies found no statistically significant difference. No studies including SDH patients met the inclusion criteria. TXA reduced the overall risk of rebleeding following nontraumatic SAH. A nonsignificant reduction in mortality was demonstrated in nontraumatic SAH without substantial indication of increased risk of ischemic lesions.
Keywords: systematic review; subarachnoid hemorrhage; subdural hemorrhage; tranexamic acid